# Indefinite integral with substitution

For my engineering math course I got a couple of exercises about indefinite integrals. I ran trought all of them but stumbled upon the following problem.

$$\int \frac{1-x}{\sqrt{1+x-2x^2}}\,dx$$

We can write $1+x-2x^2$ as $(1-x)(2x+1)$

So I got:

$$\int \frac{1-x}{\sqrt{1+x-2x^2}}\,dx = \int \frac{1-x}{\sqrt{(1-x)(2x+1)}}\,dx$$

We can also replace $1-x$ in the denominator with $\sqrt{(1-x)^2}$

$$\int \frac{1-x}{\sqrt{(1-x)(2x+1)}}\,dx = \int \frac{\sqrt{(1-x)^2}}{\sqrt{(1-x)(2x+1)}}\,dx$$

If we simplify this fraction we get:

$$\int \frac{\sqrt{1-x}}{\sqrt{2x+1}}\,dx$$

Next we apply the following substitutions

$$u = -x$$ so : $-du = dx$

We can rewrite the integral as following:

$$-\int \frac{\sqrt{1+u}}{\sqrt{1-2u}}\,du$$

Then we apply another substitution: $\sqrt{1+u} = t$ so $\frac{1}{2\sqrt{1+u}} = dt$

We rewrite: $\sqrt{1+u}$ to $\frac{1}{2}t^2 \,dt$

We can also replace $\sqrt{1-2u}$ as following:

$$\sqrt{-2t^2+3}=\sqrt{-2(1+u)+3}=\sqrt{1-2u}$$

With al these substitutions the integral has now the following form:

$$-\frac{1}{2}\int \frac{t^2}{\sqrt{-2t^2+3}}\,dt$$

Next we try to ''clean'' up the numerator:

$$-\frac{1}{2} \int \frac{t^2}{\sqrt{\frac{1}{2}(6-t^2)}} \, dt$$

$$-\frac{\sqrt{2}}{2} \int \frac{t^2}{\sqrt{6-t^2}} \, dt$$

And that's where I got stuck. I can clearly see that an arcsin is showing up in the integral but don't know how to get rid of the $t^2$.

• Have you tried to integrating by parts? Nov 27 '15 at 19:56
• @Dr.MV : My answer gives an elementary way to do this problem without integrating by parts. ${}\qquad{}$ Nov 27 '15 at 20:34
• A point often missed by students in lower-division math courses is that there is a standard technique in algebra for reducing a problem involving a quadratic polynomial with a first-degree term to a problam involving a quadratic polynomial with no first-degree term. See my answer for an explanation. ${}\qquad{}$ Nov 27 '15 at 20:38
• @michaelhardy Yes. I gave you a +1. I was focused on the OP's last ezpression, and associated question, which begs for IBP. Nov 27 '15 at 20:47
• Actually, you have arccotan showing up in the integral. (The integrand is adjacent/opposite in the obvious triangle.) Not that this is much use in finishing the integral. Nov 28 '15 at 0:24

Substitute $t = \sqrt{6} \sin(u)$, so $dt = \sqrt{6} \cos(u) du$ and the integrand becomes (up to losing the $-\frac{1}{\sqrt{2}}$ at the start) $$\sqrt{6} \int \sqrt{6} \sin^2(u) du$$

I think you can do that!

• I made this exercise initially in an latex file and apparently something went wrong during the copying. It should be $-2x^2$ instead of $-x^2$. I'm sorry... Nov 27 '15 at 20:09
• Big thank you, I think I can see now how I should finish the exercise. Nov 27 '15 at 20:17

You have: $$\int \frac{1-x}{\sqrt{1+x-2x^2}}\,dx$$ First we'll do a routine substitution: $$u = 1+x-2x^2, \qquad du = (1-4x)\,dx, \qquad \frac{-du} 4 = \left( \frac 1 4 - x \right)\, dx$$ \begin{align} \int \frac{1-x}{\sqrt{1+x-2x^2}}\,dx & = \int \frac{\frac 1 4-x}{\sqrt{1+x-2x^2}}\,dx + \int \frac{\frac 3 4}{\sqrt{1+x-2x^2}}\,dx \\[15pt] & = \frac{-1} 4 \int \frac{du}{\sqrt u} + \frac 3 4 \int \frac{dx}{\sqrt{1+x-2x^2}}. \end{align} I expect you can handle the first integral above. The second integral should make you think of completing the square: \begin{align} -2x^2 + x+1 = -2\left( x^2 - \frac 1 2 x \right)^2 + 1 & = -2\left( \overbrace{x^2 - \frac 1 2 x +\frac 1 {16}}^\text{a perfect square} \right)^2 + 1 + \frac 1 8 \\[10pt] & = -2 \left( x - \frac 1 4 \right)^2 + \frac 9 8. \end{align} Then \begin{align} \frac 9 8 -2\left( x - \frac 1 4 \right)^2 = \frac 9 8 - (2x-1)^2 & = \frac 9 8 \left( 1 - \frac 8 9 (2x-1)^2 \right) \\[10pt] & = \frac 9 8 \left( 1 - \left( \frac{2\sqrt2} 3 (2x-1) \right)^2 \right) \\[10pt] & = \frac 9 8 (1 - \sin^2\theta) \\[15pt] \frac{4\sqrt2} 3 \, dx & = d\theta \end{align} et cetera.

Let $u^2=\frac{1-x}{1+2x}$. Then $x=\frac{1-u^2}{1+2u^2}$ and $\mathrm{d}x=-\frac{6u}{(1+2u^2)^2}\,\mathrm{d}u$.

Let $\sqrt2u=\tan(\theta)$, then $\sqrt2\,\mathrm{d}u=\sec^2(\theta)\,\mathrm{d}\theta$. \begin{align} \int\frac{1-x}{\sqrt{1+x-2x^2}}\,\mathrm{d}x &=\int\frac{1-x}{\sqrt{(1-x)(1+2x)}}\,\mathrm{d}x\\ &=\int\sqrt{\frac{1-x}{1+2x}}\,\mathrm{d}x\\ &=-\int\frac{6u^2}{(1+2u^2)^2}\,\mathrm{d}u\\ &=-\frac3{\sqrt2}\int\frac{\tan^2(\theta)}{\sec^4(\theta)}\sec^2(\theta)\,\mathrm{d}\theta\\ &=-\frac3{\sqrt2}\int\sin^2(\theta)\,\mathrm{d}\theta\\ &=-\frac3{2\sqrt2}\int(1-\cos(2\theta))\,\mathrm{d}\theta\\ &=-\frac3{4\sqrt2}(2\theta-\sin(2\theta))+C\\ &=-\frac3{2\sqrt2}\left(\theta-\frac{\tan(\theta)}{1+\tan^2(\theta)}\right)+C\\ &=-\frac3{2\sqrt2}\left(\arctan\left(\sqrt2u\right)-\frac{\sqrt2u}{1+2u^2}\right)+C\\ &=\frac12\sqrt{1+x-2x^2}-\frac3{2\sqrt2}\arctan\left(\sqrt{\frac{2-2x}{1+2x}}\right)+C\\ \end{align}

Hint: When you arrived at $~\displaystyle\int\sqrt{\frac{1-x}{2x+1}}~dx,~$ you should have immediately substituted

$\dfrac{1-x}{2x+1}=u^2.~$ Then the entire integrand would have been reduced to a rational function.

• I like this idea so much that I used it in my answer ;-)
– robjohn
Nov 28 '15 at 2:01